Dynamics of SARS-CoV-2 Spread Model with Vaccine Administration and Use of Masks - Khofifah Ichawati; Budi Priyo Prawoto (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2022)
The purpose of this study was to construct and determine the dynamics of the mathematical model of the reach of SARS-CoV-2 with the provision of vaccines and the use of masks. In this study, the modified SEIR model was used with the stages of conducting a literature study on mathematical modeling of the SARS-CoV-2 virus, compiling initial assumptions, making compartment diagrams, constructing mathematical models, determining equilibrium points, determining basic reproduction numbers, conducting stability analysis and synchronization of analysis results by performing numerical simulations. In this study, two equilibrium points were obtained the disease-free equilibrium point and the endemic equilibrium point. Using the basic reproduction number, we get the stability conditions for the disease-free point and the endemic point. When the disease-free point is stable, SARS-CoV-2 will disappear from the population, while when the disease-free point unstable, SARS-CoV-2 will be exist’s in the population.